P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

High-density linkage maps and chromosome level genome assemblies unveil direction and frequency of extensive structural rearrangements in wood white butterflies (Leptidea spp.) - L. Höök; K. Näsvall; R. Vila; C. Wiklund; N. Backström (Chromosome Research, 2023)
Karyotypes are generally conserved between closely related species and large chromosome rearrangements typically have negative fitness consequences in heterozygotes, potentially driving speciation. In the order Lepidoptera, most investigated species have the ancestral karyotype and gene synteny is often conserved across deep divergence, although examples of extensive genome reshuffling have recently been demonstrated. The genus Leptidea has an unusual level of chromosome variation and rearranged sex chromosomes, but the extent of restructuring across the rest of the genome is so far unknown. To explore the genomes of the wood white ( Leptidea ) species complex, we generated eight genome assemblies using a combination of 10X linked reads and HiC data, and improved them using linkage maps for two populations of the common wood white ( L. sinapis ) with distinct karyotypes. Synteny analysis revealed an extensive amount of rearrangements, both compared to the ancestral karyotype and between the Leptidea species, where only one of the three Z chromosomes was conserved across all comparisons. Most restructuring was explained by fissions and fusions, while translocations appear relatively rare. We further detected several examples of segregating rearrangement polymorphisms supporting a highly dynamic genome evolution in this clade. Fusion breakpoints were enriched for LINEs and LTR elements, which suggests that ectopic recombination might be an important driver in the formation of new chromosomes. Our results show that chromosome count alone may conceal the extent of genome restructuring and we propose that the amount of genome evolution in Lepidoptera might still be underestimated due to lack of taxonomic sampling.

Biogeography and Connectivity Across Habitat Types and Geographical Scales in Pacific Abyssal Scavenging Amphipods - Guadalupe Bribiesca-Contreras; Thomas G. Dahlgren; Tammy Horton; Jeffrey C. Drazen; Regan Drennan; Daniel O.B. Jones; Astrid B. Leitner; Kirsty A. McQuaid; Craig R. Smith; Sergio Taboada; Helena Wiklund; Adrian G. Glover (Frontiers in Marine Science, 2021)
Recently, there has been a resurgent interest in the exploration of deep-sea mineral deposits, particularly polymetallic nodules in the Clarion-Clipperton Zone (CCZ), central Pacific. Accurate environmental impact assessment is critical to the effective management of a new industry and depends on a sound understanding of species taxonomy, biogeography, and connectivity across a range of scales. Connectivity is a particularly important parameter in determining ecosystem resilience, as it helps to define the ability of a system to recover post-impact. Scavenging amphipods in the superfamilies Alicelloidea Lowry and De Broyer, 2008 and Lysianassoidea Dana, 1849 contribute to a unique and abundant scavenging community in abyssal ecosystems. They are relatively easy to sample and in recent years have become the target of several molecular and taxonomic studies, but are poorly studied in the CCZ. Here, a molecular approach is used to identify and delimit species, and to investigate evolutionary relationships of scavenging amphipods from both abyssal plain and deep (>3000 m) seamount habitats in three APEIs (Areas of Particular Environmental Interest, i.e., designated conservation areas) in the western CCZ. A total of 17 different morphospecies of scavenging amphipods were identified, which include at least 30 genetic species delimited by a fragment of the cytochrome c oxidase subunit I (COI) barcode gene. The scavenging communities sampled in the western CCZ included the most common species ( Abyssorchomene gerulicorbis (Shulenberger and Barnard, 1976), A. chevreuxi (Stebbing, 1906), Paralicella caperesca Shulenberger and Barnard, 1976, and P. tenuipes Chevreux, 1908) reported for other ocean basins. Only four morphospecies, representing five genetic species, were shared between APEIs 1, 4, and 7. The two abyssal plain sites at APEIs 4 and 7 were dominated by two and three of the most common scavenging species, respectively, while the APEI 1 seamount site was dominated by two species potentially new to science that appeared to be endemic to the site. The presence of common species in all sites and high genetic diversity, yet little geographic structuring, indicate connectivity over evolutionary time scales between the areas, which span about 1500 km. Similar to recent studies, the differences in amphipod assemblages found between the seamount and abyssal sites suggest that ecological conditions on seamounts generate distinct community compositions.

Implications of population connectivity studies for the design of marine protected areas in the deep sea: An example of a demosponge from the Clarion‐Clipperton Zone - Sergi Taboada; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Vasiliki Koutsouveli; Nadiezhda Santodomingo; Andrew C. Dale; Craig R. Smith; Daniel O. B. Jones; Thomas G. Dahlgren; Adrian G. Glover (Molecular Ecology, 2018)
The abyssal demosponge Plenaster craigi inhabits the Clarion‐Clipperton Zone ( CCZ ) in the northeast Pacific, a region with abundant seafloor polymetallic nodules with potential mining interest. Since P. craigi is a very abundant encrusting sponge on nodules, understanding its genetic diversity and connectivity could provide important insights into extinction risks and design of marine protected areas. Our main aim was to assess the effectiveness of the Area of Particular Environmental Interest 6 ( APEI ‐6) as a potential genetic reservoir for three adjacent mining exploration contract areas ( UK ‐1A, UK ‐1B and OMS ‐1A). As in many other sponges, COI showed extremely low variability even for samples ~900 km apart. Conversely, the 168 individuals of P. craigi, genotyped for 11 microsatellite markers, provided strong genetic structure at large geographical scales not explained by isolation by distance (IBD). Interestingly, we detected molecular affinities between samples from APEI ‐6 and UK ‐1A, despite being separated ~800 km. Although our migration analysis inferred very little progeny dispersal of individuals between areas, the major differentiation of OMS ‐1A from the other areas might be explained by the occurrence of predominantly northeasterly transport predicted by the HYCOM hydrodynamic model. Our study suggests that although APEI ‐6 does serve a conservation role, with species connectivity to the exploration areas, it is on its own inadequate as a propagule source for P. craigi for the entire eastern portion of the CCZ . Our new data suggest that an APEI located to the east and/or the south of the UK ‐1, OMS ‐1, BGR , TOML and NORI areas would be highly valuable.

Characterizing baseline concentrations, proportions, and processes controlling deposition of river-transported bitumen-associated polycyclic aromatic compounds at a floodplain lake (Slave River Delta, Northwest Territories, Canada) - Matthew C. Elmes; Johan A. Wiklund; Stacey R. Van Opstal; Brent B. Wolfe; Roland I. Hall (Environmental Monitoring and Assessment, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Decoupling of female host plant preference and offspring performance in relative specialist and generalist butterflies - M. Friberg; D. Posledovich; C. Wiklund (Oecologia, 2015)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Genetic variants of TNFSF4 and risk for carotid artery disease and stroke - P. S. Olofsson; L. Å. Söderström; C. Jern; A. Sirsjö; M. Ria; E. Sundler; U. de Faire; P. G. Wiklund; J. Öhrvik; U. Hedin; G. Paulsson-Berne; A. Hamsten; et al. (Journal of Molecular Medicine, 2009)

Association between the presence of bacterial 16S RNA in prostate specimens taken during transurethral resection of prostate and subsequent risk of prostate cancer (Sweden) - O. Alexeyev; J. Bergh; I. Marklund; C. Thellenberg-Karlsson; F. Wiklund; H. Grönberg; A. Bergh; F. Elgh (Cancer Causes & Control, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Contest behaviour in the speckled wood butterfly (Pararge aegeria): seasonal phenotypic plasticity and the functional significance of flight performance - Darrell J. Kemp; C. Wiklund; H. Van Dyck (Behavioral Ecology and Sociobiology, 2006)

Efficacy of injection vaccines against Flavobacterium psychrophilum in rainbow trout, Oncorhynchus mykiss (Walbaum) - J Madetoja; L‐G Lönnström; C Björkblom; G Uluköy; G Bylund; C Syvertsen; K Gravningen; E‐A Norderhus; T Wiklund (Journal of Fish Diseases, 2006)
Efficacy of mineral oil‐based experimental injection vaccines against Flavobacterium psychrophilum were tested in rainbow trout, Oncorhynchus mykiss (Walbaum), under laboratory and field conditions. The vaccines consisted of formalin‐ or heat‐inactivated whole bacterium cell preparations of two different serotypes (Fd and Th) or a combination of serologically different F. psychrophilum (Fd and/or Th and/or Fp T ;Th). Specific antibody responses against the bacterium in plasma and skin mucus were evaluated post‐vaccination with enzyme‐linked immunosorbent assay. Efficacy of the vaccinations was determined by challenge trials to F. psychrophilum with the vaccinated rainbow trout. Significantly higher antibody levels in plasma were detected in vaccinated fish compared with mock‐vaccinated fish. Injection vaccination did not trigger specific antibody production in the skin mucus. Significantly higher survival of i.p. vaccinated fish compared with non‐vaccinated fish was observed during the challenge. The results suggest that mineral oil‐based injectable vaccines containing formalin‐ or heat‐inactivated virulent cells of F. psychrophilum effectively triggered specific antibody production and protected the fish against bacterial cold water disease.

Male butterfly investment in successive ejaculates in relation to mating system - C. J. Bissoondath; Christer Wiklund (Behavioral Ecology and Sociobiology, 1996)

Mass and production rate of ejaculates in relation to monandry/polyandry in butterflies - L. Svrd; C. Wiklund (Behavioral Ecology and Sociobiology, 1989)

Fecundity, egg weight and longevity in relation to multiple matings in females of the monarch butterfly - L. Svrd; C. Wiklund (Behavioral Ecology and Sociobiology, 1988)